Synthesis of Carboxymethyltricellulose and Its Adsorption Towards Cu2+ Ions - Ginting, Adil (Talenta Publisher, 2019)
Cellulose was isolated from plantain skin and then carboxymethylated with trichloroacetic acid which resulted a 0.9936 gram of carboxymethylcellulose. The FT-IR spectroscopy analysis of carboxymethyltricellulose indicated the –OH vibration at wavelength of 3448.72 cm-1.Moreover, a wavenumber in the region of 1026.13 cm-1 is attributed to ether vibration (-O-) and carboxyl vibration at 1651.07 cm-1. The results of morphological analysis using SEM also showed a smoother, homogeneous pore, and a larger surface area. The adsorption capability for Cu2+ ions at concentration of 100 ppm was analyzed by atomic adsorption spectrophotometer (AAS). It shows that the optimum adsorption was found to be at a 90 minutes agitation process for both carboxymethyltricellulose and cellulose with about 97.266% and 21.602% respectively.